1994
DOI: 10.1177/0146167294204004
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Person Perception Accuracy: Another Look at Self-Other Agreement

Abstract: The analysis of self-other data for the study of person perception accuracy is illustrated and discussed. Length of acquaintance, length of cohabitation, and trait empathy were investigated for their moderating effects on person perception accuracy, defined as the level of self-other agreement. Self-other agreement was computed four ways. A trait-by-trait analysis was performed twice, first using the moderator variable to form subgroups from which self-other correlations within each trait were computed and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
117
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(124 citation statements)
references
References 26 publications
6
117
1
Order By: Relevance
“…In other words, Gage and Cronbach's critique makes both difference scores and interaction effects difficult to interpret. For remedial procedures that yield more exact measures of self-other (and by extension self-self) agreement, see Bernieri, Zuckerman, Koestner, and Rosenthal, 1994. Even when interaction tests are appropriate, they do have their own share of problems. Given the importance attributed here to the distinction between main effects and interaction, investigators must be cautious about any transformation (e.g., log transformation) that may change the balance between the two.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, Gage and Cronbach's critique makes both difference scores and interaction effects difficult to interpret. For remedial procedures that yield more exact measures of self-other (and by extension self-self) agreement, see Bernieri, Zuckerman, Koestner, and Rosenthal, 1994. Even when interaction tests are appropriate, they do have their own share of problems. Given the importance attributed here to the distinction between main effects and interaction, investigators must be cautious about any transformation (e.g., log transformation) that may change the balance between the two.…”
Section: Discussionmentioning
confidence: 99%
“…One reason may be that early studies were plagued by methodological and analytic shortcomings, of the sort identified by Cronbach (1955), that have only recently begun to be rectified (Bernieri, Zuckerman, Koestner, & Rosenthal, 1994;Funder & West, 1993a). Another reason may be that extensive data about the personalities or abilities of the informants who provide personality judgments have been obtained only rarely.…”
Section: Implications For Moderatorsmentioning
confidence: 99%
“…Although acquaintance length increases accuracy in personality judgment, there is evidence that familiarity may also have a negative effect on self-other agreement (Kenny & West, 2010). The effect of length of acquaintance is neither very consistent nor large (Bernieri, Zuckerman, Koestner, & Rosenthal, 1994;Biesanz, West, & Millevoi, 2007;Gnambs, 2013;Kenny, 2004;Kurtz & Sherker, 2003;Story, 2003). This means that observing the target acting in hundreds or even thousands of similar situations improves judgement accuracy only marginally (Kenny, 2004).…”
mentioning
confidence: 99%